Access to direct-acting antivirals for the treatment of hepatitis C in a country with limited resources - S. Marciano; L. Haddad; S.M. Borzi; C. D’Amico; L.A. Gaite; M.V. Aubone; M.E. Sirotinsky; N. Ratusnu; M.S. Frola; M.C. Aparicio; B. Ríos; M.N. Anselmo; et al. (Revista de Gastroenterología de México (English Edition), 2018)
Aims: To estimate the number of patients that have access to treatment of hepatitis C with direct-acting antivirals in Argentina and evaluate the factors associated with the lack of access. Materials and methods: A cross-sectional cohort study was conducted that included all the consecutive prescriptions of direct-acting antivirals issued at health centers that participated in the ECHOTM telemedicine project directed by the Hospital Italiano de Buenos Aires, within the time frame of January 2016 and February 2017. Results: A total of 143 treatment prescriptions were included and overall access was 70% (95% CI 62-77%). The only independent factor associated with a lack of treatment access was coverage by a public healthcare system (OR 4.98 [95% CI 2.05- 12.09]). Conclusions: Patients with hepatitis C that were covered by a public healthcare system had a 4 times higher chance of not having access to treatment with direct-acting antivirals than patients covered by other healthcare systems (private insurance or the social welfare system). Resumen: Objetivos: Estimar la proporción de pacientes que acceden al tratamiento de la hepatitis C con antivirales de acción directa (AAD) en Argentina, y evaluar factores asociados a la falta de acceso. Métodos: Estudio de cohorte transversal que incluyó la totalidad de prescripciones consecutivas de AAD realizadas entre enero de 2016 y febrero de 2017 por centros de salud que participan en el proyecto de telemedicina ECHOTM dirigido por el Hospital Italiano de Buenos Aires. Resultados: Se incluyeron 143 prescripciones de tratamiento. El acceso global fue del 70% (IC95%: 62-77%). Pertenecer al sistema de salud público fue el único factor independiente asociado con la falta de acceso al tratamiento [OR 4.98 (IC95% 2.05-12.09)]. Conclusión: Los pacientes con hepatitis C pertenecientes al sistema de salud público tienen 4 veces más chances de no acceder a tratamiento con AAD que los pacientes con dependencia de otros sistemas de salud (medicina privada u obras sociales). Keywords: Direct-acting antivirals, Access, Hepatitis C, Healthcare systems, Barriers, Palabras clave: Antivirales de acción directa, Acceso, Hepatitis C, Sistemas de salud, Barreras